Alveolar macrophage transcriptomic profiling in COPD shows major lipid metabolism changes. Issue 3 (13th September 2021) - Fujii, Wataru; Kapellos, Theodore S.; Baßler, Kevin; Händler, Kristian; Holsten, Lisa; Knoll, Rainer; Warnat-Herresthal, Stefanie; Oestreich, Marie; Hinkley, Emily R.; Hasenauer, Jan; Pizarro, Carmen; Thiele, Christoph; et al.
Background: Immune cells play a major role in the pathogenesis of COPD. Changes in the distribution and cellular functions of major immune cells, such as alveolar macrophages (AMs) and neutrophils are well known; however, their transcriptional reprogramming and contribution to the pathophysiology of COPD are still not fully understood. Method: To determine changes in transcriptional reprogramming and lipid metabolism in the major immune cell type within bronchoalveolar lavage fluid, we analysed whole transcriptomes and lipidomes of sorted CD45 + Lin − HLA-DR + CD66b − Autofluorescence hi AMs from controls and COPD patients. Results: We observed global transcriptional reprogramming featuring a spectrum of activation states, including pro- and anti-inflammatory signatures. We further detected significant changes between COPD patients and controls in genes involved in lipid metabolism, such as fatty acid biosynthesis in GOLD2 patients. Based on these findings, assessment of a total of 202 lipid species in sorted AMs revealed changes of cholesteryl esters, monoacylglycerols and phospholipids in a disease grade-dependent manner. Conclusions: Transcriptome and lipidome profiling of COPD AMs revealed GOLD grade-dependent changes, such as in cholesterol metabolism and interferon-α and γ responses. AMs from COPD patients undergo GOLD grade-specific transcriptional reprogramming and acquire a complex activation profile. Among the observed changes are gene programmes involved in lipid metabolism that translate into alterations in the AM lipidome. https://bit.ly/3sYAqgd